Hyperuricemia-induced complications: dysfunctional macrophages serve as a potential bridge - Gu, Wenyi; Zhao, Jiajing; Xu, Yu (Frontiers in Immunology, 2025)
With the changes in modern life, hyperuricemia (HUA) has become a serious universal health issue, leading to rising morbidity and mortality. Characterized by elevated levels of UA, HUA has become an independent risk factor for gout, chronic kidney disease, insulin resistance, cardiovascular disease, nonalcoholic fatty liver disease, etc. As HUA is a metabolic syndrome, the immune response is likely to play an active role throughout the whole process. Moreover, macrophages, as an indispensable component of the immune system, may serve as a promising target for addressing hyperuricemia-induced inflammation. Along with their precursor cells, monocytes, macrophages play a key role in the pathogenesis of HUA, primarily through three specific aspects, all of which are associated with inflammatory cytokines. The first mechanism involves direct action on urate transporters, such as URAT1 and ABCG2. The second mechanism is the modulation of inflammation, including targeting toll-like receptors (TLRs) and the NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome. The third mechanism pertains to the effects on oxidative stress mediators. In this review, we summarize the underlying mechanisms of hyperuricemia, focusing on the effects of macrophages, therapeutic approaches, and clinical trials addressing hyperuricemia-caused dysfunction. Additionally, we highlight directions for future development, aiming to support future theoretical studies.